Minimal Mahler Measure in Real Quadratic Fields. Issue 2 (2nd April 2016) - Cochrane, Todd; Dissanayake, R. M. S.; Donohoue, Nicholas; Ishak, M. I. M.; Pigno, Vincent; Pinner, Chris; Spencer, Craig
ABSTRACT: We investigate the upper and lower bounds on the minimal Mahler measure of an irrational number lying in a particular real quadratic field.